Wideband Low-Profile 8 × 8 MIMO Antenna Based IFA Pair for Ultrathin 5G Smartphones - Hui Zhou; Di Wu; Mingmin Zhu; Yang Qiu; Guoliang Yu; Hao-Miao Zhou (International Journal of Antennas and Propagation)
In this paper, a wideband 8 × 8 MIMO antenna is proposed. The proposed antenna can realize the low profile of 4 mm and the 3.18–4.40 GHz broadband coverage only by adjusting the ground edge structure of the deformed inverted-F antenna. Based on the original antenna, the 5G new radio (NR) band n77 (3.3–4.2 GHz) can be covered without adding any structure. In addition, the coupling between the antenna elements has also been improved, decreasing from −9.7 dB to −13.37 dB. A dual-element IFA pair is simulated, fabricated, and measured, the results show the bandwidth of 3.07–4.43 GHz, and the isolation of −13.89 dB can be achieved. An eight-element MIMO antenna is formed by placing four sets of antenna pairs along the two long edges of the substrate. The experimental results show that the bandwidth is 3.18–4.40 GHz, the isolation between any two ports is better than −12.25 dB, and the total efficiency is 61.14%–93.97%. By placing the planar antenna vertically, the ground clearance of the antenna can be reduced to zero, and the performances are similar to the planar MIMO antenna. The proposed MIMO antenna has a good profile and efficient radiation performance compared with the other works, so it has an important application value in ultrathin 5G smartphones.